Carotid artery stenosis is related to cerebral small vessel disease magnetic resonance imaging burden - Stefan Stoisavljevic; Mirjana Zdraljevic; Aleksandra Radojicic; Aleksandra Pavlovic; Milija Mijajlovic (Heliyon, 2024)
Background: Cerebral small vessel disease (CSVD) encompasses conditions that affect small blood vessels of the brain, the most common being atherosclerosis. Magnetic resonance imaging (MRI) CSVD markers include lacunar strokes (LS), white matter hyperintensities (WMH), microbleeds, enlarged perivascular spaces (EPVS), and brain atrophy. Large and small cerebral arteries share an anatomical and functional connection, but the role of large vessel atherosclerosis in atherosclerotic CSVD hasn't been established. The aim of this study was to evaluate the involvement of large vessel pathology in atherosclerotic CSVD. Methods: This cross-sectional study included 98 patients treated at the Neurology Clinic of the University Clinical Center of Serbia in Belgrade, from February 2018 to December 2023, who had atherosclerotic CSVD confirmed by neuroimaging and underwent extracranial color duplex sonography. Data on patients’ gender, age, cerebrovascular risk factors (dyslipidemia, hypertension, diabetes mellitus, smoking status), ultrasonography findings (intima-media thickness - IMT, carotid and vertebral artery stenosis, and hemodynamics), and CSVD imaging markers were collected, and the CSVD MRI burden score was calculated. Results: Age correlated with LS and WMH (p < 0.05 for both). Hypertension correlated with WMH (p = 0.016), and smoking with LS (p = 0.043). Brain atrophy was more common in women (p = 0.016). The majority of patients had low-grade (<50 %) carotid stenosis. There was a strong correlation between all morphological parameters of internal carotid artery stenosis and the CSVD burden score (p < 0.05 for all). The hemodynamic parameters of internal carotid artery stenosis and morphological and hemodynamic parameters of vertebral artery stenosis didn't correlate with the CSVD burden score. Conclusions: This study shows a strong correlation between cerebral large and small vessel pathology. We recommend the use of extracranial color duplex sonography in the evaluation of patients with CSVD as a supplementary method for follow-up, as this would allow the identification of patients whose condition might progress.